Detection of Possible Medical Product-Related Infection or Pathogen Transmission—United States, 2015–2019. (October 2020) - Benowitz, Isaac; Perz, Joseph; Marders, Julia
Abstract : Background: Medications, medical devices, biological products, and other medical products can cause healthcare-associated infections related to contamination in production or transportation (intrinsic contamination) or contamination at the point of use (extrinsic contamination). Rapid identification of contaminated medical products can lead to actions to decrease further patient harm. We sought to describe events that prompted public health investigations of contaminated medical products in healthcare facilities. Methods: We reviewed records of CDC consultations with health departments and healthcare facilities from January 2015 through August 2019 to identify public health investigations in which medical products were identified as a likely source of patient infection or pathogen transmission to at least 1 patient. We collected data on products, contamination type, pathogens, route of patient exposure, healthcare setting where exposure occurred, and resulting actions. Results: There were 34 investigations involving medications (n = 15, 44%), medical devices (n = 12, 35%), biological products (n = 3, 9%), and other medical products (n = 4, 12%). Intrinsic contamination was suspected in 15 investigations (44%), with 13 (87%) based on isolation of a pathogen from unopened products and 2 (13%) based on isolation of similar pathogens from patients in contact with a medical product at multiple facilities. Extrinsic contamination was suspected in 19 investigations (56%) based on evidence of pathogen transmission at a single healthcare facility and concurrent infection control gaps at that facility supporting a mechanism of contamination. The most common pathogens prompting investigation were nontuberculous mycobacteria (n = 9, 26%), Burkholderia spp (n = 7, 21%), Klebsiella spp (n = 3, 9%), Serratia spp (n = 2, 6%), and other environmental and commensal organisms. Patients were most commonly exposed in hospitals (n = 19, 56%) and outpatient settings (n = 9, 26%). The most common patient exposures that resulted in transmission of the pathogen were infusions and injections (n = 15, 44%), diagnostic and therapeutic procedures (n = 9, 26%), and surgery (n = 5, 15%). Patient were notified and offered testing in at least 6 investigations (18%) . Interventions included product removal, healthcare provider alerts, patient notification and testing, modification of injection safety practices and other general infection control practices, correction of improper storage and handling, and changes in product design, manufacturing processes, or instructions for use. Conclusions: Public health investigations identified intrinsic and extrinsic contamination of medications, devices, and other products as a cause of healthcare-associated infections. Healthcare facilities should consider contaminated products in investigations of healthcare-associated infections, take steps to identify local infection control concerns, and alert public health authorities to events that could suggest widespread contamination. Funding: None Disclosures: None